Diabetes, pre-diabetes and cardiovascular diseases in light of the 2019 ESC Guidelines - Zandecki, Lukasz; Janion-Sadowska, Agnieszka; Kurzawski, Jacek; Janion, Marianna (Medical Studies/Studia Medyczne, 2020)
The prevalence of diabetes mellitus (DM) is steadily increasing all over the world. DM is associated with a doubling of cardiovascular (CV) risk independently of other risk factors. The European Society of Cardiology (ESC) in collaboration with the European Association for the Study of Diabetes (EASD) presented a new set of guidelines on diabetes, pre-diabetes and cardiovascular diseases at the ESC 2019 Congress in Paris. The most important changes in the guidelines include a new assessment of CV risk in DM patients, an algorithm for glucose-lowering treatment, prevention of CV diseases including new targets for the treatment of dyslipidemia taking into account CV risk and recommendations for antiplatelet/antithrombotic drugs. Furthermore, attention focused on the management of DM concomitant with coronary artery disease and heart failure, as well as individualized therapeutic strategies for diabetic patients with arterial hypertension.